A review on aluminothermic reaction of Al/ZnO system. Issue 1 (January 2018) - Maleki, Ali; Hosseini, Nazanin; Niroumand, Behzad
Abstract: Aluminothermic reaction between aluminum and a metallic oxide is worth noting, because it is applicable in some applications such as in-situ aluminum/alumina composites synthesis, welding, etc. All the metallic oxides with Gibbs free energy of formation higher than Al2 O3 can be used as the reactant oxide. Among them, the aluminothermic reaction between Al and ZnO is thermodynamically possible, because its free energy change is negative, even at room temperature. Depending on the processing method, part of the reduced Zn can be vaporized during the procedure, while the rest remains in the Al matrix. This paper attempts to review the published research works on Al/ZnO aluminothermic reaction by different processing routes giving an overview of the reactions in the liquid and solid state processes. Highlighting the technical barriers against the aluminothermic reaction propagation in Al/ZnO system, discussing the effects of different approaches on the ignition temperature as well as demonstrating how the reaction is kinetically possible even at ambient temperature are the main aspects of the present review paper. Moreover, the mechanism of the reaction and microstructural properties of the products are discussed in details. It was shown that aluminothermic reaction in the liquid state processes might be hindered kinetically due to poor wettability between aluminum and zinc oxide particles. Moreover, the results revealed that the combined mechanical and thermal treatments and mechanochemical methods facilitate the aluminothermic reaction compared to exothermic dispersion (XD). Changing the diffusion mode from bulk diffusion to grain boundary diffusion was considered as the main reason.